Respostas

2014-08-08T05:14:43-03:00
 \frac{1}{2 \sqrt{2} } = \frac{1*2 \sqrt{2} }{(2 \sqrt{2} )*(2 \sqrt{2} )}= \frac{2 \sqrt{2} }{(2 \sqrt{2)^2} }}= \frac{2 \sqrt{2} }{4*2}  =  \frac{ \sqrt{2} }{4}

:::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::
b)

 \frac{15}{2 \sqrt{10} } = \frac{15*2 \sqrt{10}}{(2 \sqrt{10})*(2 \sqrt{10})} = \frac{30 \sqrt{10}}{4*10} = \frac{3 \sqrt{10} }{4}

::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::
a ultima não consegui entender

1 5 1